Pulmonary delivery offavipiravir in rats reaches high local concentrations without causing oxidative lung Injury or systemic side effects - DURMUŞOĞLU, LÜTFİYE; YEGEN, BERRAK (My University, 2022)
Favipiravir displays a rapid viral clearance, a high recovery rate and broad therapeutic safety; however, its oral administration was associated with systemic side effects in susceptible patients. Considering that the pulmonary route could provide a high drug concentration, and a safer application with less absorption into systemic circulation, it was aimed to elucidate whether favipiravir delivered via soft-mist inhaler has any deleterious effects on lung, liver and kidney tissues of healthy rats. Wistar albino rats of both sexes (n = 72) were placed in restrainers, and were given either saline or favipiravir (1, 2.5, 5 or 10 mg/kg in 1 mL saline) by inhalation within 2 min for 5 consecutive days. On the 6th day, electrocardiographic recording was obtained, and cardiac blood and lung tissues were collected. Favipiravir did not alter cardiac rhythm, blood cell counts, serum levels of alanine transaminase, aspartate transaminase, blood urea nitrogen, creatinine, urea or uric acid, and did not cause any significant changes in the pulmonary malondialdehyde, myeloperoxidase activity or antioxidant glutathione levels. Our data revealed that pulmonary use of favipiravir via soft-mist inhaler enables a high local concentration compared to plasma without oxidative lung injury or cardiac or hepatorenal dysfunction.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; FARMAKOLOJİ VE ECZACILIK; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); PHARMACOLOGY & PHARMACY; PHARMACOLOGY & TOXICOLOGY; Life Sciences (LIFE); Farmakoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); İlaç Rehberleri; Pharmacy; Pharmacology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Drug Guides; favipiravir; antiviral; COVID-19; inhalation; pulmonary route; oxidative lung injury; hepatotoxicity; renal toxicity; cardiac toxicity; SOFT MIST(TM) INHALER; FEVER VIRUS-INFECTION; AEROSOL; T-705; INHIBITOR; TRANSMISSION; CORONAVIRUS; DEPOSITION; INTERVAL; HEALTHY; favipiravir; antiviral; COVID-19; inhalation; pulmonary route; oxidative lung injury; hepatotoxicity; renal toxicity; cardiac toxicity